2015
DOI: 10.1166/jnn.2015.8383
|View full text |Cite
|
Sign up to set email alerts
|

Secretory Leukocyte Protease Inhibitor (SLPI) Increases Focal Adhesion in MC3T3 Osteoblast on Titanium Surface

Abstract: An appropriate interaction between implanted materials and the surrounding tissue is essential for successful implantation. Titanium (Ti) and some of its alloys have been used in dentistry and orthopedics as a substitutive material for hard tissue, such as teeth or natural bone. Nevertheless, metal ions released from titanium and alloy implants have adverse biological effects on biological tissues or cells. Secretory leukocyte protease inhibitor (SLPI) promotes cell migration, proliferation and wound healing. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…A comparison of the present results with other studies indicates that SLPI can promote the differentiation and mineralization of MC3T3-E1 cells on a Ti surface. In previous studies, SLPI was shown to increase MC3T3-E1 cell adhesion to a Ti-surface as well as the proliferation of KB human oral carcinoma cells (9,13). In addition, SLPI was reported to increase mineralized nodule formation and expression of BSP, DSPP, osteocalsin, osteonectin and Col I, which are associated with odontoblast differentiation and mineralization, thereby acting as a stimulant of these processes (19).…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…A comparison of the present results with other studies indicates that SLPI can promote the differentiation and mineralization of MC3T3-E1 cells on a Ti surface. In previous studies, SLPI was shown to increase MC3T3-E1 cell adhesion to a Ti-surface as well as the proliferation of KB human oral carcinoma cells (9,13). In addition, SLPI was reported to increase mineralized nodule formation and expression of BSP, DSPP, osteocalsin, osteonectin and Col I, which are associated with odontoblast differentiation and mineralization, thereby acting as a stimulant of these processes (19).…”
Section: Discussionmentioning
confidence: 91%
“…Commercially pure titanium (Cp-Ti) discs were kindly provided by Professor Han-Cheol Choe (Department of Dental Materials, School of Dentistry, Chosun University, Gwangju, Republic of Korea). Polished Cp-Ti discs were prepared using a method described previously (9).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Highly expressed SLPI in LED-radiated RAW264.7 cells inhibits the expression of IL-1β and TNF-α (Jeong et al 2015a). Furthermore, recent studies have reported that SLPI regulates the formation of the dentin matrix and mineralization in odontoblasts, and increases adhesion and viability of osteoblasts on titanium surfaces (Jeong et al 2015b(Jeong et al , 2015c. Based on previous studies, SLPI may reduce the inflamed periodontal tissue and bone resorption.…”
Section: Introductionmentioning
confidence: 93%